1995
DOI: 10.1128/iai.63.10.3973-3979.1995
|View full text |Cite
|
Sign up to set email alerts
|

Proteases of Treponema denticola outer sheath and extracellular vesicles

Abstract: Electron microscopical observations of the oral periodontopathogen Treponema denticola show the presence of extracellular vesicles bound to the bacterial surface or free in the surrounding medium. Extracellular vesicles from T. denticola ATCC 35404, 50 to 100 nm in diameter, were isolated and further characterized. Protein and proteolytic patterns of the vesicles were found to be very similar to those of isolated T. denticola outer sheaths. They were enriched with the major outer sheath polypeptides (molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 52 publications
3
57
0
Order By: Relevance
“…Chymotrypsin-like protease activity associated with T. denticola outer membranes was due to CTLP [17,18]. As expected, and as shown in Table 1, strain CKE had greatly reduced enzymatic activity against SAAPNA, con¢rming that CTLP accounted for most of the chymotrypsin-like protease activity of T. denticola.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Chymotrypsin-like protease activity associated with T. denticola outer membranes was due to CTLP [17,18]. As expected, and as shown in Table 1, strain CKE had greatly reduced enzymatic activity against SAAPNA, con¢rming that CTLP accounted for most of the chymotrypsin-like protease activity of T. denticola.…”
Section: Resultssupporting
confidence: 74%
“…3B, and data not shown). Earlier studies implied that the high molecular mass native Msp oligomeric complex might be structurally associated with the CTLP complex [5,18]. The lack of oligomeric Msp and hexagonal array in strain CKE suggested that CTLP expression might in£uence the production or assembly of the Msp hexagonal array.…”
Section: Resultsmentioning
confidence: 99%
“…P. gingivalis vesicles were prepared according to the method of Rosen et al [24] with some modi¢cations. P. gingivalis cultures were grown in supplemented TSB and 20-ml volumes were used to prepare vesicles.…”
Section: Preparation Of Vesiclesmentioning
confidence: 99%
“…In a dentilisin-de¢cient mutant, the amount of the oligomer in the outer sheath decreases [22], and the hexagonal array disappears [23]. It is possible that the protease participates in the construction of the outer sheath component, since this protease can be isolated from membrane associated fractions such as the outer sheath and the vesicles [24]. Further study is required to determine the location of the enzyme and to evaluate the physical role of this enzyme.…”
Section: Prolyl-phenylalanine Speci¢c Proteasementioning
confidence: 99%
“…The machinery of the release of the surface material is important for its pathogenicity. Rosen et al [24] observed that the vesicles released from T. denticola were constituted of components similar to those of the outer sheath and they included dentilisin. On the other hand, Caimano et al [10] frequently observed vesicles which did not react with anti-Msp.…”
Section: Cytotoxicitymentioning
confidence: 99%